CNS TUMORS AT AKU: AN UPDATE PLUS A BRIEF DISCUSSION ON INTRAVENTRICULAR TUMORS WITH SPECIAL EMPHASIS ON CENTRAL NEUROCYTOMA. - Ahmed, Z; Azad, NS; Muzaffer, S; Hasan, SH. (Journal of Ayub Medical College Abbottabad, 2004)
Background: This paper is intended to be an update of our earlier published work on CNS tumors along with additional information on intraventricular tumors. Three cases of central neurocytoma are also discussed. Methods: An analysis conducted in the Section of Histopathology, AKU to determine the frequency of all CNS neoplasms diagnosed between Jan 1, 1994 and Dec 31, 2001. Frequency of intraventricular tumors was also determined. Histological characterization of the tumors was based on the WHO and AFIP (USA) classification systems for CNS tumors. Results: A total of 1677 CNS tumors were diagnosed during the study period. 1510(90.04%) were primary, and 167(9.96%) were metastatic. Among the primary tumors, gliomas constituted the largest category with 825 cases or 54.63% of all primary tumors. Meningothelial tumors comprised the second largest group with 364 cases or 24.10%. among other major categories, embayonal tumors, and peripheral nerve sheath tumors comprised 6.75% and 6.82% of all primary tumors. Among less common tumors, Non-Hodgkin's lymphomas and hemangioblastomas comprised 3.11% and 1.52% of all CNS tumors. Intraventricular tumors comprised 7.41% of all primary tumors. Ependymomas comprised 64.28% of all Intraventricular tumors. Conclusions: Gliomas and meningothelial tumors are the commonest group of primary CNS tumors. Metastatic tumors are quite common. KEY WORDS: Gliomas, astrocytomas, meningiomas, metastatic tumors, intraventricular tumors, central neurocytoma.